2000
DOI: 10.1111/1467-9280.00240
|View full text |Cite
|
Sign up to set email alerts
|

Is Infant-Directed Speech Prosody a Result of the Vocal Expression of Emotion?

Abstract: Many studies have found that infant-directed (ID) speech has higher pitch, has more exaggerated pitch contours, has a larger pitch range, has a slower tempo, and is more rhythmic than typical adult-directed (AD) speech. We show that the ID speech style reflects free vocal expression of emotion to infants, in comparison with more inhibited expression of emotion in typical AD speech. When AD speech does express emotion, the same acoustic features are used as in ID speech. We recorded ID and AD samples of speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
295
0
12

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(325 citation statements)
references
References 37 publications
8
295
0
12
Order By: Relevance
“…It is argued the input infants receive in affective 'baby-talk' or infant-directed speech prosody (Trainor, Austin & Desjardins, 2000), as well as the songs mothers and other caregivers sing (Bergeson & Trehub, 2002), has an impact of linguistic and musical development. Nursery rhymes and lullabies are some of the first language input that occurs with enough repetition to encourage memorization and therefore acquisition (Howle, 1989).…”
Section: First Language Acquisitionmentioning
confidence: 99%
“…It is argued the input infants receive in affective 'baby-talk' or infant-directed speech prosody (Trainor, Austin & Desjardins, 2000), as well as the songs mothers and other caregivers sing (Bergeson & Trehub, 2002), has an impact of linguistic and musical development. Nursery rhymes and lullabies are some of the first language input that occurs with enough repetition to encourage memorization and therefore acquisition (Howle, 1989).…”
Section: First Language Acquisitionmentioning
confidence: 99%
“…The SUSAS database (Hansen and BouGhazale, 1997) covers stress. The database used by Slaney and McRoberts (1998) covers mother-child interactions, which it has been argued are vocally related to emotion (Trainor et al, 2000). More directly related to emotion, but still narrowly focussed, is the Geneva groupÕs recording of travellers who had lost their luggage (see table).…”
Section: Naturalnessmentioning
confidence: 99%
“…These latter findings are in contrast to those from preference paradigms suggesting that differences in responding to ID vs. AD speech are due primarily to differences in emotional tone (e.g., Kitamura & Burnham, 1998;Singh et al, 2002;Trainor et al 2000). More recent work from our laboratory showing that infants of chronically depressed mothers do not acquire associations when happy-sounding ID speech from nondepressed mothers predicts a smiling female face suggests that nominal affective mismatches between voice and face cannot completely account for infant learning failures in this paradigm.…”
Section: Discussionmentioning
confidence: 80%
“…Trainor, Austin, and Desjardins (2000) showed that acoustic differences between ID and AD speech are minimized or disappear entirely when emotional content is held constant. Singh, Morgan, and Best (2002) provided support for this position by showing that 6-monthold infants' listening preferences for ID over AD speech were eliminated when the emotional tone was held constant.…”
Section: Discussionmentioning
confidence: 99%